Adipose tissue expression of UCP1 and PRDM16 genes and their association with postprandial triglyceride metabolism and glucose intolerance. (December 2021) - Mishra, B.K.; Madhu, S.V.; Aslam, M.; Agarwal, V.; Banerjee, B.D.
Abstract: Aims: UCP1 and PRDM16 genes, primarily involved in browning of adipose tissue that can affect lipid metabolism are also associated with diabetes risk. Therefore, we planned to study the adipose tissue expression of UCP1 and PRDM 16 genes in subjects with glucose intolerance to find out its association with postprandial triglyceride (PPTg) measures and T2DM. Methods: A total of 30 subjects were recruited in three groups i.e., NGT, prediabetes and T2DM (NDDM + known T2DM) who were matched for age, sex and BMI. An 8-hour standardized fat challenge test was performed to study lipemic responses. UCP1 and PRDM16 genes quantification in adipose tissue was performed by real-time PCR followed by SDS PAGE. Results: UCP1 gene expression in SAT was significantly lower in T2DM and prediabetes as compared to NGT group while PRDM16 gene expression was significantly lower in T2DM group as compared to NGT group. UCP1 gene expression correlated with PPTg measures as well as with glycaemic measures while PRDM16 gene expression correlated with glycaemic measures only. Conclusion: This study found downregulation of PRDM16 and UCP1 gene expression in SAT in subjects with glucose intolerance. The association of UCP1 gene expression with PPTg dysmetabolism may contribute to greater predisposition to T2DM.